PERLINDUNGAN KONSUMEN ATAS KETIDAKJELASAN INFORMASI MENGENAI LUAS APARTEMEN BOGOR VALLEY RESIDENCE BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN (STUDI KASUS: PUTUSAN NOMOR 161/Pdt.G/2016/PN.Bgr) - Tahlia Tahlia; Jeane Neltje Saly (Jurnal Hukum Adigama, 2020)
Consumer protection is an effort to guarantee legal certainty to provide legal protection for consumers.  consumer protection as the right of every consumer to use a good or service.  as in the case of housing or settlement is a basic human need and has a very strategic role in shaping the character and personality of the nation.  The construction of flats is an alternative because the construction of flats can reduce land use.  However, in implementing it, it must be able to support the growth of a place to live as a good living environment.  Thus consumers get protection, so that consumers get comfort, security, safety in consuming goods or services, the right to choose goods or services in accordance with the exchange rate and conditions and guarantees promised.  In apartments, consumers have the right and obligation to consume goods or services in accordance with what the business actor offers.  The purpose of this study is to find out and further examine the form of consumer protection for the obscure information on the area of Bogor Valley Residence apartments.